Synthesis of w-Phthalimidoalkylphosphonates - Zhou, Liang (Asian Journal of Chemistry, 2012)
A series of carbon chain growing w-phthalimidoalkylphosphonates was prepared from simple and easy available raw materials by two-step reaction. The yields can reach 58 %-64 %. Their structures are confirmed by 1H NMR correctly.